Tinerețe fără bătrânețe și viață fără de moarte: o recontextualizare teatrală (Romanian Studies Today, 2024)
The play Lexiconul amar proposes an oblique thematic connection between a well-known tale and an innovative and stimulating staging that frames the strands of the mythical characters and storyline. The alternative artistic vision of the play incorporates the separation of time and space, of youth and old age, of grotesque female monsters and enchanting realms inhabited by fairmaidens, and of the dramatic dialogue and an elaborate linguistic register. The lexicon brings into relief the story’s mystical content as well as the apprehension of an inner fantastic world that parallels the real and the immediate seen as counterpoints to the tale. Skillfully interwoven, vision and reality ballance against each other with undercutting irony that results in spontaneous stagecombustion enriched by Gothic paraphernalia, riddles, apparitions, the inadequacy of language to express a deeper reality and abrupt switches to hypochritical current verbosity.
Keywords: folklore; adaptation; grotesque; life; death